METODE MENGHAFAL AL-QUR’AN DENGAN CEPAT DAN MUDAH - Niskaromah, Niskaromah (Journal of Innovation Research and Knowledge, 2024)
Reading or memorizing the Qur’an has a very high value of worship. Each letter has a value of ten virtues in the view of Allah, therefore it is a glory for a Muslim/ muslimah to become a Ḥāfiẓ/Ḥāfiẓah and dedicate their life to serving the Qur'an. Memorizing the Qur'an requires strong intention and patience, as well as the right method according to each individual's needs. All methods must be under the guidance of a tahfiẓ instructor. Basically, memorizing the Qur'an is not too difficult, especially for those who can understand Arabic. satisfaction and inefficiency of memorization is when the memorizer does not carry out muraja'ah intensely so that he/she can not reach the level of mutqin. The basis of this research is Surah Al-Qamar verse 32 which focuses on the ease of memorizing the Al-Qur'an, regardless of method is chosenl. This research data was obtained from various literature and processed through descriptive analysis, comparison between various methods of memorizing the Qur'an with their respective characteristics and advantages. The aim of this research is to provide insight for anyone who wants to memorize the Qur'an using the right method according to their needs. In this research, 8 methods of memorizing the Al-Qur'an were found apart from the combined method of the Wahdah method and the Kitabah method. All methods refer to speed and ease of memorization. The superiority of a method is actually related to the suitability and needs of the prospective memorizer himself